إدارة أعمال الصيانة لمباني السكن الجامعي باستخدام نمذجة معلومات البناء BIM - جراد, فايز; الحسن, باسل (Latakia University Journal -Engineering Sciences Series, 2017)
حاز موضوع الصيانة على اهتمام كبير في مجال البحث العلمي وظهرت الحاجة لاستخدام تقنيات جديدة في إدارة أعمال الصيانة، حيث أن إدارة المنشأة تتعامل مع كم كبير من المعلومات المتعلقة بالصيانة والتي تتضمن الرسوم والمواصفات والقوائم والتقارير علماً أن استخدام الورقيات يؤدي إلى إنقاص الفعالية وخلق نقص في البيانات والمعلومات.نقدم في هذا البحث أداة لإدارة عملية الصيانة باستخدام BIM ،حيث سوف نشكل قاعدة بيانات على الريفت تربط بين موديلات الانتكاس للصيانة وبين مكونات البناء في النموذج ثلاثي الأبعاد المشغول على الريفت، وتعويض بيانات التقصي الخارجية الخاصة بأعمال الصيانة(تقييم الحالة، الموازنة المتوقعة للصيانة، المورد المطلوب) في هذه الموديلات، لنتوصل في نهاية هذا البحث وبالاستعانة بالإمكانيات التي توفرها لنا قاعدة البيانات الملحقة بالريفت على: بنود الصيانة في عام قادم وترتيبها حسب أهميتها وتأثيرها على المنشأة، الوصول إلى موازنة تقديرية لأعمال الصيانة الدورية وتوزيع هذه الموازنة على مختلف عناصر البناء ،وضع خطة موارد للعام القادم وصولاً إلى قاعدة معرفة لأعمال الصيانة تساعد في تحديد دورة حياة المورد ومعامل الاستبدال.Building maintenance is gaining an increasing attention in the field of scientific research and there was a need for the use of new technologies in maintenance management, , as the facility management deal with a large amount of information relating to maintenance, which includes drawings and specifications, lists, and reports, and the use of paper files leads to decrease the efficiency and create a shortage of data and information.We offer in this research tool to manage the maintenance process by using the BIM through linking deterioration models and three-dimensional model of the facility to be maintained, then compensate the external investigation data for maintenance work in these models, to get at the end of this research and with the help of the possibilities offered by Revit database to an upcoming maintenance items and arrange them according to their importance and impact on the facility , the estimated budget for the periodic maintenance and distribution of this budget on the various construction elements , the development of resources plan for next year and up to the knowledge database of maintenance will help in determining the supplier lifecycle and the coefficient of replacement.